La objetividad y el rol periodistico de los diarios machaleños durante las campañas electorales 2021 - Alarcón Acosta, Paulina Elizabeth (Machala : Universidad Técnica De Machala, 2021)
Objectivity as part of journalistic ethics is a very important part and even more so within print media. Objectivity defines how reliable or not a medium is and that is why an analysis of objectivity will be carried out as part of ethics and its impact on the journalistic role of the Machala newspapers. For this, a deep analysis will be carried out using research instruments such as: news analysis and interviews to measure with real results of the events raised and related to the subject. It is important to know how objectivity is related to professional ethics for journalists. The principle of information neutrality on the part of the mass media of public channels, substantial for the frequent evolution of the electoral campaign, is gathered in the television and radio regulations as one of the inciting principles for their work under standards such as the objectivity, impartiality and truthfulness of the news. The present work has a mixed approach because it seeks to collect, analyze and translate qualitative and quantitative data. It will be analyzed whether local newspapers use the interventionist role in their journalistic writing and how they approach the information. For this, the last week of electoral campaigns has been selected Interventionist role that will be analyzed in the journalistic notes comprises 5 variables that are described below and whose meanings are previously conceptualized by various authors. The characteristics of the journalistic role are: Interpretation, Point of view, Proposal or demand, Use of adjectives, First person. Twenty-three of the analyzed notes were from the Correo, thirteen from the newspaper El Nacional, eight from the newspaper Opinion. These notes are from the newspaper El Correo. Of the main notes are 78%, the secondary notes accounted for 18%. From the newspaper El Nacional of the variables of the interventionist role, only the interpretation was evidenced with the highest percentage of 15.38%. In addition, there was 1 note of proposal or demand that represents 4.34%. Regarding the cover notes represented by 25% Within the opening notes with 15.38%. In the newspaper Opinion as opening notes leading with 56%. As for secondary schools with 33%. Lastly, there is 1 cover story taking 1%. It is argued that objectivity as part of the journalist's ethics comes from home and is complemented by the professional's self-training to write their notes as they occur, without the need to defend their own ideals or the environment in which they work. There are those who affirm that the work of the journalist should not resort to their own criteria. You can be objective and still there is a risk that does not reflect credibility. In short: objectivity does have to do with journalistic ethics. Journalism is a channel where citizens can express their ideas about a government or a politician about something that is happening around them, journalists still only echo what they see and hear. Information is power.
La objetividad como parte de la ética periodística es una parte muy importante y aún más dentro de los medios impreso, La objetividad delimita qué tan confiable o no es un medio y es por ello que se va a realizar un análisis de la objetividad como parte de la ética y su incidencia en el rol periodístico de los diarios de Machala. Para ello, se realizará un profundo análisis utilizando los instrumentos de investigación tales como: análisis de noticias y entrevistas para realizar mediciones con resultados reales de los acontecimientos suscitados y relacionados al tema. Es importante conocer qué relación tiene para los periodistas la objetividad con la ética profesional. El principio de neutralidad informativa por parte de los medios de comunicación de cadenas públicas, sustancial para la frecuente evolución de la campaña electoral, se congrega en la normativa de la televisión y la radio como uno de los principios incitantes para su labor bajo estándares como la objetividad, imparcialidad y veracidad de las noticias. El presente trabajo posee un enfoque mixto porque busca recolectar, analizar y traducir datos cualitativos y cuantitativos. Se analizará si los diarios locales emplean el rol intervencionista en sus redacciones periodísticas y cómo ellos abordan la información. Para ello se ha seleccionado la última semana de campañas electorales Rol intervencionista que será analizado en las notas periodísticas comprende 5 variables que se describen a continuación y que sus significados están previamente conceptualizados por varios autores Las características del rol periodístico son: Interpretación, Punto de vista, Propuesta o demanda, Uso de adjetivos, Primera persona. De las notas analizadas veintitrés fueron del Correo, trece del diario El Nacional, ocho de diario Opinión. Estas notas son del diario El Correo De las notas principales son 78%, las notas secundarias representaron el 18%. Del Diario El Nacional de las variables del rol intervencionista solo se evidenció la interpretación con el mayor porcentaje del 15.38% Además, hubo 1 nota de propuesta o demanda que representa el 4.34 % En cuanto a las notas de portadas representada por el 25% Dentro de las notas de apertura con un 15.38% En el diario Opinión como notas de apertura liderando con el 56%. En cuanto a las secundarias con el 33%. Por último, hay 1 nota de portada tomando el 1%. Se sostienen que la objetividad como parte de la ética del periodista nace del hogar y se complementa con la auto capacitación del profesional para redactar sus notas tal cual ocurren, sin la necesidad de defender ideales propios o del medio en el que laboran. Hay quienes afirman que la labor del periodista no debe recurrir a su propio criterio. Se puede ser objetivo y aun así hay riesgo que no refleje credibilidad. En definitiva: la objetividad sí tiene que ver con la ética periodística. El periodismo es un canal donde los ciudadanos pueden expresar sus ideas acerca de un gobierno o un político de algo que esté sucediendo a su alrededor los periodistas y aun solo hacen eco de lo que ven escuchan. La información es poder.
Keywords: ROL PERIODISTICO; MEDIO IMPRESO; ETICA